Establishing partnership with traditional birth attendants for improved maternal and newborn health: a review of factors influencing implementation - Tina Miller; Helen Smith (BMC, 2017)
Abstract Background Recent World Health Organization recommendations recognize the important role Traditional Birth Attendants (TBAs) can play in supporting the health of women and newborns. This paper provides an analysis of key factors that affect the implementation of interventions to develop partnerships with TBAs to promote improved access to skilled care at birth. Methods We conducted a secondary analysis of 20 papers identified through two systematic reviews that examined the effectiveness of interventions to find new roles for TBAs on maternal and newborn health outcomes, as well as papers identified through a systematic mapping of the maternal health literature. The Supporting the Use of Research Evidence framework (SURE) guided the thematic analysis to explore the perceptions of various stakeholders and implementation barriers and facilitators, as well as other contextual issues. Results This analysis identified countries that have implemented interventions to support the transition from birth with a TBA to birth with a skilled birth attendant. Drawing on the experiences of these countries, the analysis highlights factors that are important to consider when designing and implementing such interventions. Barriers to implementation included resistance to change in more traditional communities, negative attitudes between TBAs and skilled attendants and TBAs concerns about the financial implications of assuming new roles. Facilitating factors included stakeholder involvement in devising and implementing interventions, knowledge sharing between TBAs and skilled birth attendants, and formalised roles and responsibilities and remuneration for TBAs. Conclusions The implementation barriers identified in this analysis could, if not addressed, prevent or discourage TBAs from carrying out newly defined roles supporting women in pregnancy and childbirth and linking them to the formal health system. This paper also identifies the factors that seem critical to success, which new programmes could consider adopting from the outset. In most cases a multi-faceted approach is needed to prepare TBAs and others for new roles, including the training of TBAs to strengthen their knowledge and skills to enable them to be able to assume new roles, alongside the sensitization of healthcare providers, communities, women and their families. Further research is required to map the transition process and stakeholder experiences in more detailed ways and to provide longer-term monitoring of existing interventions.